Changes in a Bottom-Up Vehicular Emissions Inventory and Its Impact on Air Pollution During COVID-19 Lockdown in São Paulo, Brazil - Ibarra-Espinosa, Sergio; Rehbein, Amanda; Dias de Freitas, Edmilson; Martins, Leila; Andrade, Maria de Fatima; Landulfo, Eduardo (Frontiers in Sustainable Cities, 2022)
During the lockdown associated with the severe COVID-19 crisis all cities across the world experienced changes in air pollution. The changes were registered using surface monitoring stations or satellite observations. However, modeling those changes has remained a challenge because of our limitations in the emissions estimation and also, for the numerical modeling itself. In this study, the vehicular emissions were estimated for March 2020 in the megacity of São Paulo using the model VEIN. Then, a set of WRF-Chem simulations were performed with different chemical mechanisms and initial conditions. The emissions estimation showed an increment of VOC/NO2 in downtown, due to the decrease of circulation of urban transportation and light vehicles. The chemical mechanisms covered were RADM2, CB05, CBMZ, and SAPRC99. The modeled diurnal cycles represents the variations observed in March 2020 for the periods pre-lockdown, transition and lockdown, with lower magnitude although. Our results show that the chemical mechanism CBMZ could reproduce the air pollutant concentrations. However, it is imperative to include other sources than vehicular to have a local and comprehensive emissions inventory.